ANALYSIS OF FINANCIAL STATEMENTS USING LIQUIDITY RATIO TO MEASURE FINANCIAL PERFORMANCE IN 2017-2019: (PT. Mayora Indah Tbk) - Yolanda Nofita Agustina; Hery Suprayitno (JOSAR (Journal of Students Academic Research), 2020)
The purpose of this research is to determine the financial performance of PT. Mayora Indah Tbk Company using the liquidity ratio calculation method that aims to determine the company's ability to pay or pay off corporate debt in the short term. Financial performance can be said as a material consideration of the company to find out the financial conditions that exist in the company. This type of research is a descriptive study with a qualitative analysis method approach. It is said descriptive analysis because analyzed the forms of financial statements that exist in PT. Mayora Indah Tbk Company, which has been listed on the Indonesia Stock Exchange. To obtain information related to company financial data, the researcher can look for the informations through the company's official website. The results obtained from this research are in this company within three periods in 2017 the current ratio produces a value of 238.6% while for the quick ratio of 197.8% and cash ratio of 49.21% and for 2018 current ratio of 265.45%, while for the quick ratio of 195.11% and for the cash ratio of 52.38% and the last in 2019 the value of the current ratio of 342.85% and for the quick ratio of 267.96% while the cash ratio 80%. Within three years period, it can be concluded that the company's financial condition has increased which can be seen in the figure of its liquidity ratio, it can be said that the company is able to balance between current assets and debts that exist in the company. It can also be said that the company is able to pay the company's debts.